IMPLEMENTATION OF THE LATIN AMERICAN FOREIGN POLICY VECTOR OF SPAIN THROUGH BILATERAL COOPERATION WITH THE COUNTRIES OF THE REGION - M. L. Kardanova (Современная наука и инновации)
The article considers the foreign policy of Spain in the Latin American region.